A Nandi placed outside the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
A Nandi is placed just outside the mukhamandapa (front porch), in the space between the separate rangamandapa (open type of pillared hall) and mukhamandapa. The mukhamandapa has pillars and a makara-torana (ornamental arch adorned with intricate carvings of mythical creatures) at the front. The pillars consist of mouldings at the base, shaft, and cushion abacus topped by panels that support the brackets.